2022
DOI: 10.3390/antiox11122326
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline Supplementation Reduces Blood Pressure and Myocardial Infarct Size under Chronic Intermittent Hypoxia, a Major Feature of Sleep Apnea Syndrome

Abstract: Intermittent hypoxia (IH) is a landmark of obstructive sleep apnea (OSA) at the core of the cardiovascular consequences of OSA. IH triggers oxidative stress, a major underlying mechanism for elevated blood pressure (BP) and increased infarct size. L-citrulline is an amino acid that has been demonstrated to be protective of the cardiovascular system and exert pleiotropic effects. Therefore, we tested the impact of citrulline supplementation on IH-induced increase in BP and infarct size. Four groups of rats expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…cIH had modest effects on nutritional status but with signs of altered protein metabolism. As expected, we observed anorexia, as reported in animal models of cIH (7,8,12). In the same way, previous studies reported an impact of cIH on feeding behavior that is tightly controlled by the central nervous system.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…cIH had modest effects on nutritional status but with signs of altered protein metabolism. As expected, we observed anorexia, as reported in animal models of cIH (7,8,12). In the same way, previous studies reported an impact of cIH on feeding behavior that is tightly controlled by the central nervous system.…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, no study yet has tested whether OSAS-induced cIH affects nutritional status, whereas malnutrition during obesity (i.e., sarcopenic obesity) is emerging as a major problem ( 3 5 ). First, as previously described, we validated our model by demonstrating that cIH induced an increase in hematocrit ( 12 ). The hypoxia inducible factor-1 (HIF-1)-related erythropoietin (EPO) gene transcription is an adaptative answer to the decrease in PO 2 and is responsible for an increase in hematocrit ( 17 ).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…OSA is characterized by repetitive pharyngeal collapses leading to chronic intermittent hypoxia (IH). IH is now well recognized to increase infarct size in several rodent models [6][7][8] . In myocardium, IH induces oxidative stress 8,9 and sustained HIF-1 activation 6,7,10 , leading to cardiomyocyte apoptosis through convergent mechanisms such as endoplasmic reticulum (ER) stress 7,11,12 and mitochondrial dysfunction 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…aorta, mesenteric, pulmonary and ophthalmic arteries) (Arnaud et al., 2018; Friedman et al., 2014; Mentek et al., 2018; Norton et al., 2011; Troncoso Brindeiro et al., 2007). In turn, CIH promotes irreversible oxidative protein modifications (Arnaud et al., 2018; Moya et al., 2016; Ozcan et al., 2022; Siques et al., 2014; Zhou, Wang, et al., 2014) and lipid peroxidation (Castillo‐Galán et al., 2022; Zhou, Wang, et al., 2014). This excessive ROS production can result from a CIH‐induced imbalance between pro‐ and antioxidant systems (Lavie, 2015).…”
Section: Introduction: Sleep Apnoea Chronic Intermittent Hypoxia and ...mentioning
confidence: 99%